Vanadium redox flow battery parameters optimization in a transportation microgrid: A case study. (15th March 2020) - Jefimowski, Włodzimierz; Szeląg, Adam; Steczek, Marcin; Nikitenko, Anatolii
Abstract: This paper addresses the concept of vanadium redox flow batteries as stationary energy storage for achieving optimum parameters of energy and cost-effectiveness in transportation microgrids. Such energy storage has two main purposes: to utilize the energy recovered from braking trains, and shave power peaks. With abovementioned purposes, economic feasibility is the main driver of measures to optimize the battery parameters, including joint energy and power capacity, as well as and energy management strategy parameters. The optimization results obtained from the genetic algorithm and particle swarm optimization algorithm were compared, and the comparison demonstrates that the second method operates more sufficiently. The case study shows that the implementation of the proposed battery system in a traction substation allows one to achieve approximately 7 year payback period and decrease peak power and daily consumption by 581 kW and 1.77 MWh, respectively. In addition, sensitivity analysis was conducted to determine the impact of certain factors and battery parameters on the resulting payback period. The results show that the effect of deviation of energy management strategy parameters from optimum values on payback period is four times more profound than deviation of battery parameters, which demonstrates how important energy management strategy is. Graphical abstract: Image 1010 Highlights: A simple EMS to control VRFB dedicated to transportation systems is developed. An original approach to VRFB battery parameters and EMS optimization is proposed. A case study for real parameters of the railway line is conducted, resulting in 7 years payback period. Sensitivity analysis for the variation of the uncertain parameters is conducted.